Composite metal hydroxide nanosheet as well as preparation method and application thereof
High-entropy multimetal hydroxide nanosheets were prepared by using magnesium hydroxide nanosheet templates and ion exchange method, which solved the problem of difficult synthesis and improved the electrochemical performance and cycle stability of supercapacitor electrode materials.
Patent Information
- Application Number
- CN202410430024.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2025-10-21
AI Technical Summary
The synthesis of existing two-dimensional high-entropy hydroxide nanosheets is difficult, and their cycle stability and rate performance are insufficient when used as electrode materials for supercapacitors.
High-entropy multimetal hydroxide nanosheets were prepared at room temperature using magnesium hydroxide nanosheets as sacrificial templates via ion exchange. The difference in solubility product between transition metal salts and magnesium hydroxide was utilized to form uniformly distributed composite metal hydroxide nanosheets.
The uniform distribution and stability of high-entropy hydroxide nanosheets were achieved, which improved the electrochemical performance and cycle stability of supercapacitors, making them suitable as energy storage electrode materials for supercapacitors.
Smart Images

Figure CN120817637A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanostructure preparation, and in particular to composite metal hydroxide nanosheets and a preparation method and application thereof. Background Art
[0002] Transition metal hydroxides are widely used nanomaterials, enjoying crucial and widespread applications in electrocatalysis, water purification, and energy storage electrode materials. However, the performance of single-metal transition metal hydroxides sometimes falls short of practical application requirements. When used as electrode materials, hydroxides suffer from poor cycling stability and rate performance due to their microstructural instability and low electrical conductivity.
[0003] Entropy plays a crucial role in chemical reactions, and a significant amount of fundamental research is dedicated to understanding the enthalpy-entropy relationship in molecular reactions. In 2004, two research groups proposed a new alloying method, introducing a single-phase solid solution alloy composed of at least five primary metallic elements in equimolar ratios, also known as a high-entropy alloy (HEA). HEA is characterized by five key effects: thermodynamically, the high entropy effect; kinetically, the slow diffusion effect; structurally, the lattice distortion effect; the performance cocktail effect; and structurally, high stability.
[0004] High-entropy hydroxides have the characteristics of variable structure, a wide range of controllable chemical compositions, and rich functional properties. Their large composition space can easily optimize the properties of interest. In recent years, the research and application of high-entropy oxides have attracted more and more widespread interest.
[0005] Supercapacitor is a new type of energy storage device between traditional capacitors and rechargeable batteries. As a new type of energy storage device, it has the characteristics of high energy density, high power density, long service life, wide operating temperature range and fast charging speed.
[0006] Transition metal-based hydroxides are one of the commonly used electrode materials because of their many comprehensive properties such as high theoretical capacity, good Faradaic reaction performance, abundant sources, and environmental friendliness. However, single hydroxides as supercapacitor electrode materials still have the problem of poor cycle life, which greatly limits their practical application value.
[0007] CN 113149086 B discloses a two-dimensional high-entropy hydroxide array catalyst and its electrocatalytic nitrogen fixation and ammonia synthesis method. The steps for synthesizing the two-dimensional high-entropy hydroxide array catalyst are: 1) dissolving five equimolar metal salts in a mixed solvent of water and ethanol; 2) placing a three-dimensional substrate in the solution described in step 1 and conducting a hydrothermal reaction in a sealed container; and 3) washing and drying the resulting product to obtain the array. The array material obtained by this method can be directly used as a catalytic electrode, requiring no additional binder or substrate. It has a continuously adjustable electronic structure and an ultra-thin two-dimensional sheet structure. However, this method requires heating for the reaction and requires that the salt must be an acetylacetonate, which is highly restrictive and the reaction conditions are relatively harsh. Furthermore, the array is grown on a nickel foam substrate, requiring support. CN 114214730 A discloses a preparation method and product of a high-capacity single-crystal positive electrode battery material, relating to the technical field of single-crystal high-entropy battery materials. The method comprises using an ultrafine needle-shaped iron-rich high-entropy material as a crystal nucleus to produce a rod-shaped single-crystal oxide to increase the lithium ion diffusion rate. The method specifically comprises preparing a battery-grade raw material solution, synthesizing the ultrafine needle-shaped iron-rich high-entropy material crystal nucleus under high pH conditions, continuing to grow, adding lithium, and sintering into a single-crystal powder product. From another perspective, the ultrafine needle-shaped iron-rich high-entropy material is used as a crystal nucleus to produce a rod-shaped single-crystal oxide, thereby shortening the diffusion path of lithium ions between the electrolyte and the internal lattice of the single crystal, thereby solving the problem of relatively difficult lithium ion diffusion in single-crystal positive electrode materials. However, the synthesis of the high-entropy material in this application still requires a precipitant and pH control, and the method is not universally applicable. CN 109967081 A discloses a high-activity, carbon deposition-resistant methane dry gas catalyst and a preparation method thereof. The catalyst precursor is a high-entropy nanomaterial. Specifically, a stable sol having a nanosheet structure is prepared by a precipitation method. A divalent inorganic metal salt and a trivalent inorganic metal salt are mixed to obtain a mixed salt, which is dissolved in water to form a mixed salt solution. The mixed salt solution is added to an aqueous precipitant solution, stirred and reacted for 0.5-6 hours, and separated and washed to obtain a precipitate. The mixed salt is composed of an active metal precursor salt and a metal oxide precursor salt. The precipitate is redispersed in water and hydrothermally treated to obtain a stable sol having a nanosheet structure (precursor nanosheets). This technical solution requires the additional addition of a precipitant and requires co-precipitation and hydrothermal treatment to obtain the final nanosheets. The preparation process is cumbersome, not conducive to large-scale production, and lacks universal applicability. Summary of the Invention
[0008] The purpose of the present invention is to address the problem of difficulty in synthesizing two-dimensional high-entropy hydroxide nanosheets and provide composite metal hydroxide nanosheets and their preparation method and application. The method uses magnesium hydroxide nanosheets as sacrificial templates and an ion exchange method based on the difference in hydroxide solubility product to prepare high-entropy multi-metal (five metals or more) hydroxide nanosheets, and applies them to energy storage electrode materials such as supercapacitors.
[0009] In order to achieve the above object, the present invention provides a composite metal hydroxide nanosheet, wherein the composite metal hydroxide nanosheet contains magnesium and a transition metal element;
[0010] The transition metal elements are selected from four or more of manganese, iron, cobalt, nickel, copper and zinc.
[0011] Preferably, the thickness of the composite metal hydroxide nanosheets is 1-10 nm.
[0012] A second aspect of the present invention provides a method for preparing the above-mentioned composite metal hydroxide nanosheets, the method comprising the following steps:
[0013] (1) mixing magnesium oxide with water, filtering, and drying the filtered solid to obtain nano-flaky magnesium hydroxide;
[0014] (2) mixing a transition metal salt with water to obtain a transition metal salt solution, then mixing the nano-plate-shaped magnesium hydroxide with the transition metal salt solution, reacting, and then drying;
[0015] Wherein, the transition metal salt is selected from four or more of manganese salt, iron salt, cobalt salt, nickel salt, copper salt and zinc salt.
[0016] Preferably, in step (1), the method for preparing magnesium oxide comprises: heating the magnesium source to 600-1000° C. at a heating rate of 2-20° C. / min and calcining for 1-5 hours.
[0017] Preferably, the calcination atmosphere is air.
[0018] Preferably, the flow rate of the air is 100-1000 mL / min.
[0019] Preferably, in step (1), the weight ratio of magnesium oxide to water is 1:5-15.
[0020] Preferably, in step (1), the mixing time is 24-48 hours.
[0021] Preferably, in step (2), the concentration of the transition metal salt in the transition metal salt solution is 0.01-3 mol / L.
[0022] Preferably, in step (2), the molar ratio of the amount of the nano-flaky magnesium hydroxide to the total amount of the transition metal salt is 1:1-2.
[0023] Preferably, in step (2), the reaction time is 10 min-48 h.
[0024] The third aspect of the present invention provides the use of the above-mentioned composite metal hydroxide nanosheets in energy storage electrode materials.
[0025] The preparation method of the present invention uses ultra-thin magnesium hydroxide nanosheets as a sacrificial template and, at room temperature without adding any precipitant, uses ion exchange to form five or more composite metal hydroxide nanosheets using multiple transition metal salt precursors with similar hydroxide solubility products. The nanomaterial obtained by this method has a uniform distribution of multiple metals and can be used as an electrode material for supercapacitors. Due to the synergistic effect of multiple ions, the electrochemical performance can be improved. In addition, due to the uniqueness of the preparation method, the trace amount of Mg remaining in the hydroxide matrix is reduced. 2+ This can stabilize the hydroxide structure in the KOH electrolyte cycle stability test, demonstrating the superiority of this method. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 is an SEM image of the composite metal hydroxide nanosheets obtained in Example 1;
[0027] Figure 2 is a TEM image of the composite metal hydroxide nanosheets obtained in Example 1;
[0028] Figure 3 This is the EDS image of the composite metal hydroxide nanosheets obtained in Example 1;
[0029] Figure 4 This is a graph showing the thickness test results of the composite metal hydroxide nanosheets obtained in Example 1;
[0030] Figure 5 is the XRD pattern of the composite metal hydroxide nanosheets obtained in Examples 1-4;
[0031] Figure 6 1 is a graph showing the cyclic voltammetric stability test results of the composite metal hydroxide nanosheets obtained in Example 1;
[0032] Figure 7 This is a graph showing the cyclic voltammetry stability test results of the composite metal hydroxide nanosheets obtained in Comparative Example 3. DETAILED DESCRIPTION
[0033] The following describes the specific embodiments of the present invention in detail with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention and are not intended to limit the present invention.
[0034] The endpoints of the ranges and any values disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoints of each range, the endpoints of each range and individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered to be specifically disclosed herein.
[0035] In one aspect, the present invention provides a composite metal hydroxide nanosheet, wherein the composite metal hydroxide nanosheet contains magnesium and a transition metal element;
[0036] The transition metal elements are selected from four or more of manganese, iron, cobalt, nickel, copper and zinc.
[0037] The composite metal hydroxide nanosheets described in the present invention are high-entropy (multi-metal) hydroxide nanosheets, which contain magnesium and at least four transition metal elements, and the elements are evenly distributed. Under the synergistic effect of multiple metal elements, the electrochemical performance of the composite metal hydroxide nanosheets can be improved.
[0038] Preferably, the thickness of the composite metal hydroxide nanosheets is 1-10 nm.
[0039] In the composite metal hydroxide nanosheets of the present invention, the ratio between the transition metal elements will also affect the electrochemical properties of the finished product, and the ratio between the transition metal elements can be reasonably controlled according to needs.
[0040] In a preferred case, when the transition metal elements are selected from four elements of manganese, iron, cobalt, nickel, copper and zinc, they are respectively recorded as transition metal element A, transition metal element B, transition metal element C and transition metal element D, and the molar ratio of transition metal element A, transition metal element B, transition metal element C and transition metal element D is 1-5:1-5:1-5:1-5.
[0041] In a preferred case, when the transition metal element is selected from five elements of manganese, iron, cobalt, nickel, copper and zinc, they are respectively recorded as transition metal element A, transition metal element B, transition metal element C, transition metal element D and transition metal element E, and the molar ratio of transition metal element A, transition metal element B, transition metal element C, transition metal element D and transition metal element E is 1-5:1-5:1-5:1-5:1-5.
[0042] In a preferred case, when the transition metal salt used is selected from manganese, iron, cobalt, nickel, copper and zinc, the molar ratio of manganese, iron, cobalt, nickel, copper and zinc is 1-5:1-5:1-5:1-5:1-5:1-5.
[0043] In a more preferred embodiment, the molar amounts of various transition metal elements in the composite metal hydroxide nanosheets are the same.
[0044] A second aspect of the present invention provides a method for preparing the above-mentioned composite metal hydroxide nanosheets, the method comprising the following steps:
[0045] (1) mixing magnesium oxide with water, filtering, and drying the filtered solid to obtain nano-flaky magnesium hydroxide;
[0046] (2) mixing a transition metal salt with water to obtain a transition metal salt solution, then mixing the nano-plate-shaped magnesium hydroxide with the transition metal salt solution, reacting, and then drying;
[0047] Wherein, the transition metal salt is selected from four or more of manganese salt, iron salt, cobalt salt, nickel salt, copper salt and zinc salt.
[0048] In the method of the present invention, the magnesium oxide can be purchased commercially or prepared in-house.
[0049] When the magnesium oxide is self-made, preferably, in step (1), the preparation method of the magnesium oxide comprises: heating the magnesium source to 600-1000° C. at a heating rate of 2-20° C. / min and calcining for 1-5 hours.
[0050] In a specific embodiment, the heating rate can be 2°C / min, 5°C / min, 10°C / min, 15°C / min or 20°C / min.
[0051] In a specific embodiment of the present invention, the calcination temperature can be 600°C, 700°C, 800°C, 900°C or 1000°C.
[0052] In specific cases, the calcination time can be 1 h, 2 h, 3 h, 4 h or 5 h.
[0053] In the present invention, there is no special requirement for the selection of the magnesium source, as long as it can provide magnesium element and obtain magnesium oxide after roasting. In a specific embodiment, the magnesium source is selected from one or more of basic magnesium carbonate, light magnesium oxide, magnesium nitrate hexahydrate and magnesium chloride hexahydrate.
[0054] Preferably, the calcination atmosphere is air.
[0055] Preferably, the flow rate of the air is 100-1000 mL / min, specifically 100 mL / min, 200 mL / min, 400 mL / min, 500 mL / min, 600 mL / min, 800 mL / min or 1000 mL / min.
[0056] When the magnesium oxide used in the present invention is commercially available, it is easy to absorb moisture in the air and react to form substances such as magnesium carbonate, and magnesium carbonate dissolved in water will interfere with the formation of nano-flaky magnesium hydroxide. Therefore, when the magnesium oxide used is commercially available or has been left for a period of time, it is preferably calcined under the same conditions to remove the influence of substances such as magnesium carbonate contained therein.
[0057] Preferably, in step (1), the weight ratio of magnesium oxide to water is 1:5-15, specifically 1:5, 1:7, 1:10, 1:12 or 1:15.
[0058] Preferably, in step (1), in order to ensure that magnesium oxide and water are fully mixed to generate magnesium hydroxide, the mixing time needs to be controlled to be 24-48 hours.
[0059] In a specific embodiment of step (1), the mixing time can be 24 hours, 28 hours, 32 hours, 36 hours, 40 hours, 44 hours or 48 hours.
[0060] In a preferred embodiment, in step (2), the concentration of the transition metal salt in the transition metal salt solution will have a certain influence on the properties of the final finished material. Therefore, it is more appropriate to control the concentration of the transition metal salt in the transition metal salt solution to 0.01-3 mol / L, specifically 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, 0.25 mol / L or 0.3 mol / L.
[0061] Preferably, in step (2), in order to ensure that the final composite metal hydroxide nanosheets have good electrochemical properties, the molar ratio of the amount of the nano-flaky magnesium hydroxide to the total amount of the transition metal salt is 1:1-2, specifically 1:1, 1:1.2, 1:1.5, 1:1.7 or 1:2.
[0062] The present invention utilizes the difference in solubility products between different metal ions to prepare composite metal hydroxide nanosheets by ion exchange. Therefore, the selected transition metal salt is preferably a water-soluble substance, and the solubility product of the transition metal ions in the selected transition metal salt should be significantly different from that of magnesium ions, and the solubility products of various transition metal ions should be close.
[0063] In the present invention, there is no special requirement for the selection of the manganese salt, which can be used to provide manganese ions, for example, it can be one or more of manganese chloride tetrahydrate, manganese sulfate pentahydrate, manganese nitrate hexahydrate and manganese acetate trihydrate.
[0064] In the present invention, there is no special requirement for the selection of the iron salt, which can be used to provide iron ions, for example, it can be one or more of ferric chloride hexahydrate, ferrous sulfate heptahydrate, ferric nitrate nonahydrate and ferrous acetate tetrahydrate.
[0065] In the present invention, there is no special requirement for the selection of the cobalt salt, which can be used to provide cobalt ions, for example, it can be one or more of cobalt chloride hexahydrate, cobalt nitrate hexahydrate, cobalt sulfate heptahydrate and cobalt acetate tetrahydrate.
[0066] In the present invention, there is no special requirement for the selection of the nickel salt, which can be used to provide nickel ions, for example, it can be one or more of nickel chloride hexahydrate, nickel acetate tetrahydrate, nickel nitrate hexahydrate and nickel sulfate hexahydrate.
[0067] In the present invention, there is no special requirement for the selection of the copper salt, which can be used to provide copper ions, for example, it can be one or more of copper chloride dihydrate, copper acetate monohydrate, copper sulfate pentahydrate and copper nitrate trihydrate.
[0068] In the present invention, there is no special requirement for the selection of the zinc salt, as long as it can be used to provide zinc ions, for example, it can be one or more of zinc chloride dihydrate, zinc acetate dihydrate, zinc sulfate heptahydrate and zinc nitrate hexahydrate.
[0069] In the present invention, the amounts of the various transition metal salts used can be appropriately selected based on the required content of the transition metal elements in the prepared composite metal hydroxide nanosheets and the electrochemical properties.
[0070] In a preferred case, when the transition metal salt used is selected from four of manganese salts, iron salts, cobalt salts, nickel salts, copper salts and zinc salts, they are respectively recorded as transition metal salt A, transition metal salt B, transition metal salt C and transition metal salt D, and the molar ratio of transition metal salt A, transition metal salt B, transition metal salt C and transition metal salt D is 1-5:1-5:1-5:1-5.
[0071] In a preferred case, when the transition metal salt used is selected from five of manganese salts, iron salts, cobalt salts, nickel salts, copper salts and zinc salts, they are respectively recorded as transition metal salt A, transition metal salt B, transition metal salt C, transition metal salt D and transition metal salt E, and the molar ratio of transition metal salt A, transition metal salt B, transition metal salt C, transition metal salt D and transition metal salt E is 1-5:1-5:1-5:1-5:1-5.
[0072] In a preferred embodiment, when the transition metal salt is selected from manganese salts, iron salts, cobalt salts, nickel salts, copper salts and zinc salts, the molar ratio of the manganese salts, iron salts, cobalt salts, nickel salts, copper salts and zinc salts is 1-5:1-5:1-5:1-5:1-5:1-5.
[0073] In a more preferred embodiment, the molar amounts of the various transition metal salts used in step (2) are the same.
[0074] In a preferred embodiment, in order to ensure sufficient exchange of metal ions, in step (2), the reaction time is 10 min-48 h, specifically 10 min, 2 h, 10 h, 15 h, 20 h, 25 h, 30 h, 35 h, 40 h, 45 h or 48 h.
[0075] Preferably, the reaction in step (2) is carried out under stirring, wherein the stirring rate is 700-800 rpm, specifically 700 rpm, 720 rpm, 750 rpm, 770 rpm or 800 rpm.
[0076] The drying temperature in step (2) of the present invention is room temperature, and the drying time is 12-24 hours.
[0077] In a specific embodiment, the drying time in step (2) can be 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours.
[0078] In the present invention, the room temperature refers to 20-30°C.
[0079] Compared with other two-dimensional high-entropy hydroxide preparation technologies, the method of the present invention is simple and universal, does not require the addition of additional precipitants and surfactants, can be carried out at room temperature, and is conducive to scale-up production research; the composite metal hydroxide nanosheets prepared by this method, due to the particularity of the preparation method, have a trace amount of magnesium hydroxide self-doped into the material matrix in situ, which can stabilize the electrode material structure in alkaline electrolyte.
[0080] The third aspect of the present invention provides the use of the above-mentioned composite metal hydroxide nanosheets in energy storage electrode materials.
[0081] The composite metal hydroxide nanosheets described in the present invention can be applied to energy storage electrode materials. Transition metal hydroxides are commonly used electrode materials with high theoretical capacity, good Faradaic reaction performance, abundant raw material sources, and environmentally friendly comprehensive characteristics. Therefore, the composite metal hydroxide nanosheets of the present invention have good application prospects as electrode materials for supercapacitor energy storage.
[0082] The present invention will be described in detail below through examples, but the scope of protection of the present invention is not limited thereto.
[0083] In the following examples, room temperature refers to 25°C.
[0084] Example 1
[0085] 3 g of basic magnesium carbonate was heated to 750 ° C at a heating rate of 10 ° C / min, and calcined at 750 ° C for 2 h (the calcination atmosphere was air, and the air flow rate was 500 mL / min) to obtain magnesium oxide; 2 g of the calcined magnesium oxide was placed in 10 g of deionized water, stirred and mixed for 24 h, and then filtered. The filtered solid was dried to obtain nano-flaky magnesium hydroxide; transition metal salts (0.70 g of ferrous sulfate heptahydrate, 0.73 g of cobalt nitrate hexahydrate, 0.73 g of nickel nitrate hexahydrate, 0.6 g of copper nitrate trihydrate and 0.72 g of manganese nitrate hexahydrate, ferrous sulfate heptahydrate, cobalt nitrate hexahydrate, Nickel nitrate, copper nitrate trihydrate and manganese nitrate hexahydrate (in a molar ratio of 1:1:1:1:1) are added to deionized water and mixed evenly to obtain a transition metal salt solution, wherein the concentration of the transition metal salt in the transition metal salt solution is 1.5 mol / L, and then 0.73 g of nano-flaky magnesium hydroxide is added to the transition metal salt solution and mixed, and the molar ratio of the amount of nano-flaky magnesium hydroxide to the total amount of the transition metal salt is 1:1. The reaction is stirred at room temperature for 3 hours at a stirring rate of 750 rpm to obtain a uniform sol, which is washed and dried at room temperature for 24 hours to obtain composite metal (magnesium, iron, cobalt, nickel, copper, and manganese) hydroxide nanosheets A1.
[0086] Example 2
[0087] 3 g of basic magnesium carbonate was heated to 750 ° C at a heating rate of 15 ° C / min, and calcined at 750 ° C for 2 h (the calcination atmosphere was air, and the air flow rate was 300 mL / min) to obtain magnesium oxide; 2 g of the calcined magnesium oxide was put into 10 g of deionized water, stirred and mixed for 24 h, and then filtered. The filtered solid was dried to obtain nano-flaky magnesium hydroxide; transition metal salts (0.70 g of ferrous sulfate heptahydrate, 1.46 g of cobalt nitrate hexahydrate, 0.73 g of nickel nitrate hexahydrate, 0.6 g of copper nitrate trihydrate and 0.72 g of manganese nitrate hexahydrate, ferrous sulfate heptahydrate, cobalt nitrate hexahydrate, Nickel nitrate, copper nitrate trihydrate and manganese nitrate hexahydrate (in a molar ratio of 1:2:1:1:1) are added to deionized water and mixed evenly to obtain a transition metal salt solution, wherein the concentration of the transition metal salt in the transition metal salt solution is 1 mol / L, and then 0.73 g of nano-flaky magnesium hydroxide is added to the transition metal salt solution and mixed, and the molar ratio of the amount of nano-flaky magnesium hydroxide to the total amount of transition metal salt is 1:1.2. The reaction is stirred at room temperature for 24 hours at a stirring rate of 700 rpm to obtain a uniform sol, which is washed and dried at room temperature for 24 hours to obtain composite metal (magnesium, iron, cobalt, nickel, copper, and manganese) hydroxide nanosheets A2.
[0088] Example 3
[0089] 3 g of basic magnesium carbonate was heated to 750 ° C at a heating rate of 5 ° C / min, and calcined at 750 ° C for 2 h (the calcination atmosphere was air, and the air flow rate was 1000 mL / min) to obtain magnesium oxide; 2 g of the calcined magnesium oxide was placed in 10 g of deionized water, stirred and mixed for 24 h, and then filtered. The filtered solid was dried to obtain nano-flaky magnesium hydroxide; transition metal salts (0.87 g of ferrous sulfate heptahydrate, 0.91 g of cobalt nitrate hexahydrate, 0.91 g of nickel nitrate hexahydrate and 0.75 g of copper nitrate trihydrate, ferrous sulfate heptahydrate, cobalt nitrate hexahydrate, Hydrated nickel nitrate and copper nitrate trihydrate (in a molar ratio of 1:1:1:1) are added to deionized water and mixed uniformly to obtain a transition metal salt solution, wherein the concentration of the transition metal salt in the transition metal salt solution is 3 mol / L, and then 0.73 g of nano-flaky magnesium hydroxide is added to the transition metal salt solution and mixed, wherein the molar ratio of the amount of nano-flaky magnesium hydroxide to the total amount of the transition metal salt is 1:1. The reaction is stirred at room temperature for 3 hours at a stirring rate of 800 rpm to obtain a uniform sol, which is washed and dried at room temperature for 24 hours to obtain composite metal (magnesium, iron, cobalt, nickel, and copper pentametallic) hydroxide nanosheets A3.
[0090] Example 4
[0091] The method of Example 1 was followed, except that basic magnesium carbonate was replaced by light magnesium oxide, and the stirring reaction time was 48 h to obtain composite metal hydroxide nanosheets A4.
[0092] Example 5
[0093] The method of Example 1 was followed, except that basic magnesium carbonate was replaced by magnesium chloride hexahydrate, and the stirring reaction time was 20 minutes to obtain composite metal hydroxide nanosheets A5.
[0094] Example 6
[0095] The method of Example 1 was followed, except that the stirring reaction time was 10 min, to obtain composite metal hydroxide nanosheets A6.
[0096] Example 7
[0097] The method of Example 1 was followed, except that the concentration of the transition metal salt in the transition metal salt solution was 2 mol / L, to obtain composite metal hydroxide nanosheets A7.
[0098] Example 8
[0099] 3 g of basic magnesium carbonate was heated to 750 ° C at a heating rate of 20 ° C / min, and calcined at 750 ° C for 2 h (the calcination atmosphere was air, and the air flow rate was 200 mL / min) to obtain magnesium oxide; 2 g of the calcined magnesium oxide was put into 10 g of deionized water, stirred and mixed for 24 h, and then filtered. The filtered solid was dried to obtain nano-flaky magnesium hydroxide; transition metal salts (0.68 g of ferric chloride hexahydrate, 0.60 g of cobalt chloride hexahydrate, 0.60 g of nickel chloride hexahydrate, 0.43 g of copper chloride dihydrate and 0.50 g of manganese chloride tetrahydrate, ferric chloride hexahydrate, cobalt chloride hexahydrate, hexahydrate) were added to the mixture. Nickel chloride, copper chloride dihydrate and manganese chloride tetrahydrate (in a molar ratio of 1:1:1:1:1) are added to deionized water and mixed evenly to obtain a transition metal salt solution, wherein the concentration of the transition metal salt in the transition metal salt solution is 2.5 mol / L, and then 0.73 g of nano-flaky magnesium hydroxide is added to the transition metal salt solution and mixed, and the molar ratio of the amount of nano-flaky magnesium hydroxide to the total amount of the transition metal salt is 1:1. The reaction is stirred at room temperature for 3 hours at a stirring rate of 800 rpm to obtain a uniform sol, which is washed and dried at room temperature for 24 hours to obtain composite metal (magnesium, iron, cobalt, nickel, copper, and manganese) hydroxide nanosheets A8.
[0100] Example 9
[0101] 3 g of basic magnesium carbonate was heated to 750° C. at a heating rate of 15° C. / min, and calcined at 750° C. for 2 h (the calcination atmosphere was air, and the air flow rate was 700 mL / min) to obtain magnesium oxide; 2 g of the calcined magnesium oxide was placed in 10 g of deionized water, stirred and mixed for 24 h, and then filtered, and the filtered solid was dried to obtain nano-flaky magnesium hydroxide; transition metal salts (0.7 g of ferrous sulfate heptahydrate, 0.71 g of cobalt sulfate heptahydrate, 0.66 g of nickel sulfate hexahydrate, 0.63 g of copper sulfate pentahydrate and 0.61 g of manganese sulfate pentahydrate, ferrous sulfate heptahydrate, cobalt sulfate heptahydrate, hexahydrate) were added to the mixture. Nickel sulfate, copper sulfate pentahydrate and manganese sulfate pentahydrate (in a molar ratio of 1:1:1:1:1) are added to deionized water and mixed evenly to obtain a transition metal salt solution, wherein the concentration of the transition metal salt in the transition metal salt solution is 0.5 mol / L, and then 0.73 g of nano-flaky magnesium hydroxide is added to the transition metal salt solution and mixed, and the molar ratio of the amount of nano-flaky magnesium hydroxide to the total amount of the transition metal salt is 1:1. The reaction is stirred at room temperature for 3 hours at a stirring rate of 780 rpm to obtain a uniform sol, which is washed and dried at room temperature for 24 hours to obtain composite metal (magnesium, iron, cobalt, nickel, copper, and manganese) hydroxide nanosheets A9.
[0102] Comparative Example 1
[0103] Transition metal salts (0.70 g of ferrous sulfate heptahydrate, 0.73 g of cobalt nitrate hexahydrate, 0.73 g of nickel nitrate hexahydrate, 0.6 g of copper nitrate trihydrate and 0.72 g of manganese nitrate hexahydrate) were added to deionized water and mixed evenly to obtain a transition metal salt solution, wherein the concentration of the transition metal salt in the transition metal salt solution was 2 mol / L. Then 1.80 g of hexamethylenetetramine was added and stirred at room temperature for 0.5 h to obtain a uniform sol, which was then transferred to a crystallization kettle for hydrothermal reaction at a temperature of 120° C. for 12 h. The obtained product was washed and dried at room temperature for 24 h to obtain composite metal (iron, cobalt, nickel, copper and manganese five metals) hydroxide nanosheets D1.
[0104] Comparative Example 2
[0105] Transition metal salts (0.70 g of ferrous sulfate heptahydrate, 0.73 g of cobalt nitrate hexahydrate, 0.73 g of nickel nitrate hexahydrate, 0.6 g of copper nitrate trihydrate and 0.72 g of manganese nitrate hexahydrate) were added to deionized water and mixed evenly to obtain a transition metal salt solution, wherein the concentration of the transition metal salt in the transition metal salt solution was 2 mol / L. Then 0.6 g of sodium hydroxide was added, and the mixture was stirred and reacted at room temperature for 6 h at a stirring rate of 750 rpm to obtain a uniform sol. The mixture was reacted at room temperature for 6 h. The obtained product was washed and dried at room temperature for 24 h to obtain a composite metal (iron, cobalt, nickel, copper and manganese five metals) hydroxide D2 with a granular morphology.
[0106] Comparative Example 3
[0107] Transition metal salts (0.70 g of ferrous sulfate heptahydrate, 0.73 g of cobalt nitrate hexahydrate, 0.73 g of nickel nitrate hexahydrate, 0.6 g of copper nitrate trihydrate and 0.72 g of manganese nitrate hexahydrate) were added to deionized water and mixed evenly to obtain a transition metal salt solution, wherein the concentration of the transition metal salt in the transition metal salt solution was 2 mol / L. Then 0.8 g of urea was added and the mixture was stirred and reacted at room temperature for 6 h at a stirring rate of 750 rpm to obtain a uniform sol, which was then transferred to a crystallization kettle for hydrothermal reaction at a temperature of 120°C and a time of 12 h. The obtained product was washed and dried at room temperature for 24 h to obtain composite metal (iron, cobalt, nickel, copper and manganese five metals) hydroxide nanosheets D3.
[0108] Test Example 1
[0109] 1. Scanning electron microscope (SEM) and transmission electron microscope (TEM) were used to detect the morphology of A1-A9, and EDS element mapping was used to test A1-A9. The SEM image of A1 is shown in the figure below. Figure 1 As shown in the TEM image Figure 2 As shown, the EDS diagram is as follows Figure 3 As shown, according to the test results, the product obtained in the embodiment is flaky, and the metal elements are evenly distributed therein; through TEM and EDS mapping characterization analysis, it is found that a small amount of Mg(OH)2 component exists in the obtained material;
[0110] 2. Atomic force microscopy (AFM) was used to characterize the thickness of A1-A9, where the results of A1 are as follows: Figure 4 As shown, according to Figure 4 It can be seen that the average thickness of A1 is 3.57 nm, and the thicknesses of A2-A9 are also between 1-10 nm;
[0111] 3. XRD was used to characterize A1-A9, and the results of Examples 1-4 were as follows: Figure 5 As shown, from Figure 5 It can be seen that the crystal phase of the product obtained in the embodiment is amorphous;
[0112] 4. The contents of various metal elements in A1-A9 and D1-D3 were detected by inductively coupled plasma spectrometry (ICP-OES). The results are shown in Table 1.
[0113] Table 1
[0114]
[0115] According to the results in Table 1, the content of each transition metal element in Examples 1-9 is uniform.
[0116] Test Example 2
[0117] 1. A1-A9, D1-D3 were mixed with conductive carbon black and binder (polytetrafluoroethylene) in a weight ratio of 75:20:5 respectively and dispersed in anhydrous ethanol to obtain electrode slurry. The obtained electrode slurry was applied on carbon cloth and then dried in an oven at 80°C for 24 hours to obtain electrode plates. The obtained electrode plates were pressed under a pressure of 10 MPa to obtain a mass loading of about 1.0 mg / cm 2 The working electrode was used to measure the electrochemical properties of the samples using cyclic voltammetry (CV) and constant current charge-discharge curves. The results of the electrode electrochemical performance (capacitance (F / g) at different voltages) are shown in Table 2.
[0118] 2. Cyclic voltammetry stability test of A1 and D3 was carried out using electrochemical workstation. The electrochemical performance stability spectrum of A1 is shown as follows: Figure 6 As shown, the electrochemical performance stability spectrum of D3 is as follows Figure 7 As shown, according to Figure 6 and Figure 7 Yes, in the 10,000-cycle continuous charge and discharge test, the stability of A1 is much better than that of D3. This is due to the presence of magnesium hydroxide in A1. Due to the small amount of Mg(OH)2 component in the alkaline electrolyte, there is an ionization equilibrium, namely: Therefore, in a 6.0M KOH electrolyte, the ionization reaction proceeds to the left, causing the component to exist mainly in the form of Mg(OH)2, which is a non-electrochemically active component. Therefore, its presence is beneficial to stabilizing the structure of the composite metal hydroxide nanosheets and improving its structural stability, thereby benefiting the improvement of the cycle stability of the resulting composite material for supercapacitors. At the same time, Mg(OH)2 is a highly stable component in alkaline electrolytes, and the residual Mg(OH)2 can act as a "binder" to stabilize the microstructure and provide a stable morphology to resist long-term charging / discharging.
[0119] Table 2
[0120]
[0121] According to the results in Table 2, compared with the comparative example, Examples 1-9 have better electrochemical properties as electrode materials. Compared with Examples 1-4, Examples 8 and 9 have slightly decreased electrode material performance because the metal salt precursors are all chlorides or sulfates; the stirring rate of Example 6 is short, and the ion exchange reaction is not as thorough as that of Example 1, resulting in slightly reduced performance; the higher concentration of the metal salt solution in Example 7 has little effect on the performance; by comparing the capacitance of the examples and the comparative example, at low voltage (1V), the capacitance of the comparative example is much smaller than that of the examples, which shows that this scheme can obtain high-performance supercapacitor electrode materials.
[0122] The preferred embodiments of the present invention have been described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, various simple variations of the technical solution of the present invention may be made, including combining the various technical features in any other appropriate manner. These simple variations and combinations should also be regarded as disclosed in the present invention and fall within the scope of protection of the present invention.
Claims
1. A composite metal hydroxide nanosheet, characterized in that The composite metal hydroxide nanosheets contain magnesium and transition metal elements; The transition metal elements are selected from four or more of manganese, iron, cobalt, nickel, copper and zinc.
2. The composite metal hydroxide nanosheet according to claim 1, characterized in that The thickness of the composite metal hydroxide nanosheet is 1-10 nm.
3. A method for preparing the composite metal hydroxide nanosheet according to claim 1 or 2, characterized in that: The method comprises the following steps: (1) mixing magnesium oxide with water, filtering, and drying the filtered solid to obtain nano-flaky magnesium hydroxide; (2) mixing a transition metal salt with water to obtain a transition metal salt solution, then mixing the nano-plate-shaped magnesium hydroxide with the transition metal salt solution, reacting, and then drying; Wherein, the transition metal salt is selected from four or more of manganese salt, iron salt, cobalt salt, nickel salt, copper salt and zinc salt.
4. The method according to claim 3, characterized in that In step (1), the preparation method of magnesium oxide comprises: heating a magnesium source to 600-1000° C. at a heating rate of 2-20° C. / min and calcining the mixture for 1-5 hours.
5. The method according to claim 4, characterized in that The calcination atmosphere is air.
6. The method according to claim 5, characterized in that The flow rate of the air is 100-1000 mL / min.
7. The method according to claim 3, characterized in that In step (1), the weight ratio of magnesium oxide to water is 1:5-15.
8. The method according to claim 3 or 7, characterized in that In step (1), the mixing time is 24-48 hours.
9. The method according to claim 3, characterized in that In step (2), the concentration of the transition metal salt in the transition metal salt solution is 0.01-3 mol / L.
10. The method according to claim 3 or 9, characterized in that In step (2), the molar ratio of the amount of the nano-flaky magnesium hydroxide to the total amount of the transition metal salt is 1:1-2.
11. The method according to claim 3, characterized in that In step (2), the reaction time is 10 min-48 h.
12. Use of the composite metal hydroxide nanosheets according to claim 1 or 2 in energy storage electrode materials.
Citation Information
Patent Citations
High activity and carbon deposition resistant catalyst for reforming of dry methane gas and preparation method thereof
CN109967081A
Two-dimensional high-entropy hydroxide array catalyst and its electrocatalytic nitrogen fixation and ammonia synthesis method
CN113149086B
Preparation method of high-capacity single-crystal positive electrode battery material and product
CN114214730A